Wood Pellet as a Renewable Source of Energy From Production to Consumption - Abdoli, Mohammad Ali (University of Tehran Science and Humanities Series,, 2018)
This book takes the reader on a journey from the moment that raw wood material enters the factory to the final pellet consumption. It starts by reviewing biomass application and its role for the future development of renewable energies, discussing different biomass conversion methods as alternatives to direct utilization. The second chapter then comprehensively examines densification processes, with a focus on the pelleting process. Chapter three further elaborates on the pelleting process, including an overview of the pellet structure and properties, and the history of this process. The subsequent chapters provide a detailed account of the production process from raw material delivery to final distribution, addressing the chemical and physical quality, and presenting measurement methods and standards. In the final chapters, the authors describe in detail the pellet combustion process and emissions.